Investigating and boosting walkability in Sulaimani’s mixed-use streets: Jamal Irfan street as a case study - Jamal, Mariwan; Khasraw, Wanawsha; Khabat, Shaey; Mohammed-Amin, Rozhen K. (Kurdistan Journal of Applied Research, 2017)
Walkable cities, neighborhoods, and streets promote good health. A growing number of research show compelling evidence about the positive impacts of walkable neighborhoods and streets on everything from real-estate values to health, mental well-being, crime rate, safety feeling, creativity, and even making cities more democratic. Walkability has health, environmental, and economic benefits. For example, several studies found that people in walkable neighborhoods have a higher amount of physical activity and were substantially less likely to be overweight or obese than those living in low-walkable neighborhoods. Walkable neighborhoods and streets incorporate features that promote regular walking, cycling and public transit use. While the city of Sulaimani in general suffers from lack of walkable neighborhoods and streets, due to many factors including incomplete streets, some of the city’s neighborhoods and streets have potential for becoming effective walkable neighborhoods and streets. The recent mixed use developments and re-developments in some of the areas and streets in the city have attracted a large number of people and increased the necessity of making those areas and streets more pedestrian-friendly and walkable. This research aims at investigating walkability characters in Sulaimani city’s recently developed mixed-use streets through closely examining a representing case study, Jamal Irfan street. The research then proposes strategies, guidelines, and urban design interventions that make those streets more pedestrian friendly according to urban design standards.